Study on Black Phosphorus Characteristics Using a Two-Step Thinning Method - Chen, D (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
A mild two-step method of black phosphorus (BP) flake thinning was demonstrated in this article. Slight ultraviolet–ozone (UVO) radiation followed by an argon plasma treatment was employed to oxidize mechanically exfoliated BP flakes and remove the surface remains of previous ozone treatment. The annealing process introduced aims to reduce impurities and defects. Low damage and efficient electronic devices were fabricated in terms of controlling the thickness of BP flakes through this method. These results lead to an important step toward the fabrication of high-performance devices based on two-dimensioned materials. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.